2005
DOI: 10.1001/archinte.165.9.986
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Alcohol Consumption by Brief Alcohol Intervention in Primary Care

Abstract: Focusing on patients in primary care, our systematic review and meta-analysis indicated that brief alcohol intervention is effective in reducing alcohol consumption at 6 and 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
426
3
28

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 606 publications
(469 citation statements)
references
References 48 publications
12
426
3
28
Order By: Relevance
“…Our findings also reveal that the drinking status of the control group changed little at 2 post-tests, but the drinking problems of the experimental group continued improving, supporting a 12-month effect of the brief alcohol intervention. Six-to 12-month effects of brief alcohol interventions were also supported in meta-analyses of studies on reducing alcohol consumption in primary settings (Bertholet et al, 2005) and among heavy alcohol drinkers as outpatients, inpatients, and in the general population (Wilk et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Our findings also reveal that the drinking status of the control group changed little at 2 post-tests, but the drinking problems of the experimental group continued improving, supporting a 12-month effect of the brief alcohol intervention. Six-to 12-month effects of brief alcohol interventions were also supported in meta-analyses of studies on reducing alcohol consumption in primary settings (Bertholet et al, 2005) and among heavy alcohol drinkers as outpatients, inpatients, and in the general population (Wilk et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…A series of interactive text messages and images were designed (by DWF) using messaging theory 46, 47, 48, social cognition models 49, systematic reviews of interventions to tackle alcohol problems 7, 8, 9 and systematic reviews of text message intervention studies 26, 27, 29. The intervention adopted a motivational interviewing approach of helping individuals to decide for themselves that they wish to change, rather than advising them to change 50.…”
Section: Methodsmentioning
confidence: 99%
“…This may be related to binge drinking that is more prevalent among disadvantaged men 4, 5. Although there is extensive evidence showing that brief interventions are effective in reducing alcohol consumption 6, 7, 8, 9, no studies have specifically addressed disadvantaged groups. Brief interventions may need to be tailored for disadvantaged people, because they are less likely to engage in health promotion programs 10.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent procedures, the need to provide contact information for follow-up contacts and the desire to meet outcome expectations or please a researcher might influence treatment and control patients [7][8][9]. Regression to the mean [10,11] probably explains a large portion of 'improvement' seen in all patients who qualified for the study based on a relatively high screening score. In addition to these potential problems, Saitz [3] notes that the magnitude of improvement in outcomes reported by Madras et al are unrealistic and are five times the best absolute outcomes reported for randomized controlled trials (RCTs) (e.g.…”
Section: Introductionmentioning
confidence: 99%